Archaeobotany and Bioanthropology: The Potential of VR and 3D Printing in the Enhancement of Archaeological Organic Remains - Roberta Manzollino; Giulia Chellini; Paola La Torre; Saverio Giulio Malatesta; Marco Raoul Marini; Claudia Moricca (Proceedings)
The term bioarchaeology refers to the study of archaeological remains of organic origin, including human and botanical remains, which are highly informative for reconstructing past human–environment relationships. However, they are not very tangible, either because of ethical issues or their reduced size. Using novel technologies, such as modeling, 3D printing, and virtual reality, these remains have been made accessible, manipulable, and inclusive. The objective of this work is the technological enhancement of bioarchaeological remains through the development of an innovative, non-destructive, non-invasive, and reproducible protocol. In this way, more effective dissemination of the information obtained from studying these materials is possible, making them more accessible to different audiences.